2018
DOI: 10.2478/gsr-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Protein Fibrils in Microgravity

Abstract: Deposits of insoluble protein fibrils in human tissue are associated with amyloidosis and neurodegenerative diseases. Different proteins are involved in each disease; all are soluble in their native conformation in vivo, but by molecular self-assembly, they all form insoluble protein fibril deposits with a similar cross β-sheet structure. This paper reports the results of an experiment in molecular self-assembly carried out in microgravity on the International Space Station (ISS). The Self-Assembly in Biology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…At the same time, the literature on microgravity effects is scarce. Morphological [ 36 ] and kinetical alterations [ 37 ] were reported for samples fibrillating in microgravity. Interestingly, flows and gravitational forces are directional, and it was reported that the geometry of the applied forces plays a role in the destabilization of the protein [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the literature on microgravity effects is scarce. Morphological [ 36 ] and kinetical alterations [ 37 ] were reported for samples fibrillating in microgravity. Interestingly, flows and gravitational forces are directional, and it was reported that the geometry of the applied forces plays a role in the destabilization of the protein [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was speculated that the changes seen were due to lower transport rates for larger aggregates in this convection-limited environment. Furthermore, Bell et al 108 investigated molecular self-assembly on the ISS and reported that lysozyme protein fibrils showed a distinctly different morphology. The fibrils formed in microgravity were shorter, straighter, and thicker than those formed in ground-based studies.…”
Section: Microgravitymentioning
confidence: 99%
“…Many biological processes as well as biomolecular self-assembly depend on gravity. For example, in microgravity, proteins form larger crystals with fewer defects 14 , and amyloid fibrils nucleate and grow differently in simulated microgravity 15,16 . Comparing virus assembly in orbiter flight studies against ground controls, polyomavirus assembled into larger and more homogeneous capsomeres but did not form capsid-like structures 17 .…”
Section: Introductionmentioning
confidence: 99%